PHARMACOGNOSTICAL, PHYSICOCHEMICAL AND HPTLC EVALUATION OF TRIVRITTADI KWATHA: A POLYHERBAL FORMULATION - Rao, *Rajdip; Thakar, A.B.; Bhatt, N.N.; CR, Harisha; Shukla, V.J. (International Journal of Ayurveda and Pharma Research, 2017)
Background: Trivrittadi kwatha is mentioned in Charaka samhita as a therapeutic formulation to treat Kushtha (Skin disorder). The skin diseases are considered in the umbrella of Kushtha. There is no definite line of treatment is given in the classics but the Seers have described Shwitra (Vitiligo) under the kushtha and line of treatment should be done like Kushtha. Vitiligo affects 1% of the population worldwide but management is till unsatisfactory. Trivrittadi kwatha contains Trivritta (Operaculina turpethum (Linn.), Danti (Boliospermum montanum Muell-Arg.) and Triphala which is compound of Haritaki (Terminalia chebula), Bibhitaki (Terminalia belerica) and Amalaki (Emblica officinalis). This polyherbal formulation has enough potential to do Virechana (therapeutic purgation). Method: Trivrittadi kwatha powder was evaluated for their pharmacognostical and pharmaceutical analysis. Results: Microscopic characters were found of Trivritta, Danti, Haritaki, Bibhitaki and Amalaki. Results obtained in pharmaceutical parameters of Trivrittadi kwatha powder like loss on drying 8.2 % w/w, Ash value 6.268 %, Alcohol soluble extract 91.5 % w/w etc. are within limit mentioned by Ayurvedic Pharmacopoeia of India. High Performance Thin Layer Chromatography (HPTLC) profile of Trivrittadi kwatha powder showed similarities in number of spots. Conclusion: From the study, data developed can be espoused for laying down the standards for Trivrittadi kwatha.